Wielka praca nad mową (Fragment homilii wygłoszonej 6 czerwca 1991 roku podczas Mszy św. w Olsztynie w ramach czwartej pielgrzymki Jana Pawła II do Polski) - Paweł II, Jan (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2012)
The eighth commandment, “You shall not bear false witness against your neighbor,” stresses that being truthful is a duty to be observed by human beings in their relations with others, as well as throughout their presence in social life. The commandment in question in particular reflects the fact that man was created in the image and likeness of God, who is truth. Thus human actions must be in accord with the requirements of truthfulness. Truth is good, whereas lies, hypocrisy and falsehood are evil, which human beings experience in various dimensions of their lives. The question of truthfulness in social and public life was particularly significant in Poland after 1989. After the breakdown of communism, the freedom of speech was restored and diverse views and standpoints could be publicly expressed. However, neither the freedom of speech, nor public expression of one’s views as such, can guarantee the freedom of the word that is thus being said. The freedom of speech is of little use if the words being said are not free, if they are tethered by egocentrism, deceit, guile, or even the hatered and contempt of others, of human beings who have a different skin color, a different religion or different views. There is little benefit from speech or from writing unless the words they employ are meant to seek, express and share truth rather than win debates or defend one’s position at any cost, even if it should be completely wrong. Sometimes though words may express truth in a way that is humiliating to truth itself. For instance, one may happen to be telling the truth in order to justify one’s lie. A grave disorder is introduced in social life through attempts to employ truth in the service of deceit. Truth is humiliated whenever it is not told for the sake truth itself or whenever there is no love for the human being inherent in it. The eighth commandment cannot be observed in social life unless it presupposes kindness, mutual trust and respect for all the differences that enrich the community. The climate of falsehood and deceit in social life results from treating human beings as objects or means to some end; it enters social life with every word said in order to negatively affect others, as in the case of defamation or slander, or to introduce moral disorder. Throughout the communist period Poles were forbidden to say truth publicly, and after 1989 social life needed to be made free from falsehood. The virtue of veracity needed to be restored in order that it might shape human life as well as the media and the worlds of culture, politics and economy. While the eighth commandment proclaims that truth is a good for human beings and that each human being has the right to truth, there happen to be rightful exceptions to this rule. We admire those who will not reveal the truth even in the face violence being done to them, if they know that this truth might harm innocent human beings. Oppressors have no right to truth in such cases. In the contemporary society, one can view the media as either bearing witness to truth or not doing so. The power of modern media calls for the responsibility for the words they transmit. If the media do not accept this responsibility, they become evil and start manipulating the public opinion, much as they may be giving the impression to the contrary. One can see thus that the eighth commandment opens the human being to a whole range of existential dimensions. Yet bearing witness to truth is costly. Jesus Christ said: “For this reason I was born, and for this reason I came into the world – to testify to the truth” (J 18:37). While it is true that human beings are free to tell untruth, they will not be truly free unless they speak truth. Christ gives a clear response to this situation: „The truth will set you free” (J 8:32). Thus one might say that human life is an aspiration to freedom through truth. This fact is very important in the current times. While we relish the freedom of speech, as well as other freedoms it implies, we tend to forget that essentially there is no freedom without truth. Only truth can make us free. Outside truth, freedom is no longer freedom, but merely its appearance which makes the human being vulnerable to enslavement. Summarized by Dorota Chabrajska